Specialized Predation on Oribatid Mites by Two Species of the Ant Genus Myrmecina (Hymenoptera: Formicidae) - Keiichi Masuko (Psyche: A Journal of Entomology)
Specialized predation on oribatid mites was confirmed in two Japanese species of the myrmicine genus Myrmecina, the first instance in the Formicidae. Using the mouthparts and legs, a worker skillfully tears a hole in the oribatid body and gives the partly dismembered prey to a larva. During food preparation workers bend the gaster forward deeply and raise their anterior body thus making the working posture stable; both seem necessary for handling such round slippery prey as oribatid mites. The larva of Myrmecina has a peculiarly elongate head which it inserts into an oribatid body and consumes the contents.